(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify the tendency towards perfection among educational counselors, as well as to identify the significance of the difference in positive flexibility in terms of gender. To achieve the objectives of the research, a scale of 45 items developed by Al-Ubaidi (2020) was adopted to collect data. It was applied to a random sample of 150 male and female counselors affiliated with the six directorates in the Baghdad Governorate for the academic year (2023-2024). The results showed that the research sample of educational counselors tends to perfection. There are no statistically significant differences between male and female counselors in the tendency toward perfection. The researcher came out with a set of recommendations and suggestions in light of the research results.